Compositional effects of O-SII capital buffers and the role of monetary policy - Alessio Reghezza; Costanza Rodriguez D'Acri; Martina Spaggiari; Giuseppe Cappelletti (European Central Bank (ECB), 2020)
We investigate the impact of macroprudential capital requirements on bank lending behaviour across economic sectors, focusing on their potentially heterogenous effects and transmission channel. By employing confidential loan-level data for the euro area over 2015-18, we find that the reaction of banks to structural capital surcharges depends on the level of the required capital buffer and the economic sector of the borrowing counterpart. Although tighter buffer requirements correspond to stronger lending contractions, targeted banks curtail their lending towards credit institutions the most, while leaving loan supply to non-financial corporations almost unchanged. We find that this lending is mitigated when banks resort to central bank funding. These results have important policy implications as they provide evidence on the impact of macroprudential policy frameworks and their interaction with unconventional monetary policies.
Keywords: E51; E58; E60; G21; G28; 330; Macroprudential Policy; Unconventional Monetary Policy; Credit Supply; Loan-level Data; Large Exposure